Synthesis and in vitro anticancer properties of a new La(III) coordination polymer. Issue 8 (17th April 2020) - Hao, Xinyu; Li, Yan; Liu, Xiaoyi; Ren, Jing'ao; Shi, Conghao; Liu, Yuanhui; Zou, Dengfeng; Li, Qiaoyun; Yang, Gaowen
Abstract: {La(pytza)3 (H2 O)2 ·2H2 O} n derived from 5-(4-pyridyl)tetrazole-2-acetic acid (Hpytza) has been synthesized by a solvothermal reaction of Hpytza and La(NO3 )3 ·6H2 O. In this compound, neighboring La 3+ ions are doubly bridged by two pytza ligands in a μ 1, 3 -COO syn-syn mode to form a binuclear unit, then adjacent binuclear units are doubly bridged to give a 1-D ladder-like chain. In vitro MTT assay on HeLa cells demonstrates that Hpytza is nontoxic while {La(pytza)3 (H2 O)2 ·2H2 O} n has a low half inhibitory concentration (IC50 ) of 18.2 μg/mL. Furthermore, cell migration across a 2-D artificial gap indicates that this compound can effectively inhibit the migration of HeLa cells, suggesting its potential to interfere with the tumor metastasis in vivo . Graphical Abstract: